Determination of Thermal Conductivity and Porosity of Composite Panels from Fibers, Bagasse Powder and Polypropylene (PP) Plastic Waste - Azca Aryadiva Mahengga; Yenni Darvina; Ramli Ramli; Fadhila Ulfha Jhora (Department of Physics, Universitas Negeri Padang, 2023)
Global warming causes temperatures on the earth's surface to increase. High temperatures during the day will make the temperature in the room of the residential house increase. The impact will affect the warmth of residents. One of the causes of the increase in indoor temperature is due to the absorption of solar heat by the components of the walls and roof. One alternative that can be done is the manufacture of composite panels that act as heat insulators using bagasse fibers, bagasse powder and the matrix of polypropylene plastic waste with low thermal conductivity, and high porosity. The composition of the composite varies the percentage of fibers and powders with a fixed percentage of polypropylene plastic waste of 90%. The percentage variation of polypropylene plastic waste of bagasse fiber and powder used is 100%:0%:0%, 90%:10%:0%, 90%:8%:2%, 90%:6%:4%, 90%:4%:6%, 90%:2%:8%, and 90%:0%:10%. Based on the test results, successive thermal conductivity values were 0.226715 W/moC, 0.16241 W/moC, 0.13543 W/moC, 0.09582 W/moC, 0.11457 W/moC, 0.15351 W/moC, 0.18276 W/moC. The porosity values of successive samples were 0.63116%, 2.84024%, 3.36151%, 3.85179%, 3.24880%, 3.09383%, 2.65145%. From the test results, it was obtained that variation 4 had the highest thermal conductivity value with a value of 0.09582 W / moC. while the highest porosity value was obtained in variation 4 with a value of 3.85179%. Composite panels with a variation of 4, and a variation of 5 are optimum variations that can be used as a good heat insulation material.